Dirty limit scattering behind the decreased anisotropy of doped YBa2Cu3O7−δ thin films. (5th April 2016) - Malmivirta, M; Palonen, H; Inkinen, S; Yao, L D; Tikkanen, J; Huhtinen, H; Jha, R; Awana, V P S; van Dijken, S; Paturi, P
Abstract: We measured the resistivity of pulsed-laser-deposited BaCeO3 (BCO)-doped YBCO thin films containing spherical BCO particles in fields up to 30 T. The average diameter of the particles depends on the dopant concentration being below 4 nm in all the samples. Raised values of the upper critical field, B c 2, were observed in all the samples. Additionally, the parameter γ, describing the electron mass anisotropy, decreased from 6.2 in the undoped sample to 3.1 in the 8 wt.% BCO-doped sample. These results can be explained by the increased number of defects decreasing the mean free path of electrons and thus lowering the coherence length, which in turn increases B c 2 .